Integrative 16S rRNA and transcriptome analysis reveals the molecular mechanisms underlying salt- tolerant germination in highland barley (Hordeum vulgare var. coeleste Linnaeus) seeds - Ren, Panrong; Qiao, Yan; Wang, Jie (Frontiers in Plant Science, 2025)
Salt stress is a critical abiotic factor that impairs crop seed germination and limits agricultural productivity. Elucidating the mechanisms governing salt tolerance is essential for development of salt-tolerant crop varieties. In this investigation, 217 accessions of highland barley (Hordeum vulgare var. coeleste Linnaeus) were evaluated. Germination assays conducted under 200 mmol/L and 500 mmol/L NaCl conditions identified a salt-tolerant variety 37 and a salt-sensitive variety 44. By integrating transcriptome sequencing, 16S rRNA sequencing, and Na+/K+ content analysis, we systematically investigated the molecular mechanisms underlying salt-tolerant germination in highland barley seeds. Our findings revealed that the salt-tolerant variety 37 maintained a high germination rate of 98% under 500 mmol/L NaCl stress, with lower Na+ accumulation (4.24 g/kg) and a lower Na+/K+ ratio (2.59) compared to the salt-sensitive variety 44 (Na+ accumulation: 4.89 g/kg, Na+/K+ ratio: 3.62). Analysis of 16S rRNA sequencing data showed a significant increase in the abundance of the endophytic bacterium Brevundimonas in salt-tolerant variety 37 under high-salt conditions, which was positively correlated with K+ content. In contrast, the dominant bacterium Rhodococcus in salt-sensitive variety 44 exhibited a positive correlation with Na+ content and the Na+/K+ ratio. Transcriptome sequencing identified 1,467 and 1,644 differentially expressed genes (DEGs) in salt-tolerant variety 37 and salt-sensitive variety 44, respectively. Pathway enrichment analysis indicated that DEGs in salt-tolerant variety 37 were primarily associated with “potassium ion homeostasis” and “response to oxidative stress”. Weighted gene co-expression network analysis (WGCNA) identified 5 co-expression modules, among which the MEyellow module was correlated with Na+ content (r = 0.59). Ten core genes were identified, including WRKY transcription factor (HORVU.MOREX.r3.3HG0268090) and receptor protein kinase (RPK; HORVU.MOREX.r3.4HG0331910). A total of 174 HvRPK genes were identified, distributed across 7 chromosomes with a predominant localization on chromosome 2. These genes exhibited functional conservation and were involved in salt stress signaling pathways. Phylogenetic, collinearity, and cis-element analyses further supported their regulatory role in salt stress responses. This study clarifies the key mechanisms underlying salt-tolerant germination in highland barley seeds, providing valuable insights and genetic resources for the molecular breeding of salt-tolerant crops.